The role of dynamic and diffusion weighted magnetic resonance imaging in differentiating malignant and benign portal vein thrombosis (Annals of Medical Research, 2021)
None
Keywords: Dynamic MRI; Diffusion-Weighted Imaging; Apparent Diffusion Coefficient; Portal Vein; Thrombus.